Variation in treatment associated with life expectancy in a population‐based cohort of men with early‐stage prostate cancer. Issue 23 (17th July 2014) - Daskivich, Timothy J.; Lai, Julie; Dick, Andrew W.; Setodji, Claude M.; Hanley, Janet M.; Litwin, Mark S.; Saigal, Christopher; ,
Abstract : BACKGROUND: Men with major comorbidities are at risk for overtreatment of prostate cancer due to uncertainty regarding their life expectancy. We sought to characterize life expectancy and treatment in a population‐based cohort of men with differing ages and comorbidity burdens at diagnosis. METHODS: We sampled 96, 032 men aged ≥66 years with early‐stage prostate cancer who had Gleason scores ≤7 and were diagnosed during 1991 to 2007 from the Surveillance, Epidemiology, and End Results‐Medicare database. We calculated cumulative incidence of other‐cause mortality and determined treatment patterns among subgroups defined by age and Charlson comorbidity index scores. RESULTS: Overall, life expectancy was <10 years (10‐year other‐cause mortality rate, >50%) for 50, 049 of 96, 032 men (52%). Life expectancy differed by age and comorbidity score and was <10 years for men ages 66 to 69 years with Charlson scores ≥2, for men ages 70 to 74 years with Charlson scores ≥1, and for all men ages 75 to 79 years and ≥80 years. Among those who had a life expectancy <10 years, treatment was aggressive (surgery, radiation, or brachytherapy) for 68% of men aged 66 to 69 years, 69% of men aged 70 to 74 years, 57% of men aged 75 to 79 years, and 24% of men aged ≥80 years. Among these men, aggressive treatment was predominantly radiation therapy (50%, 53%, 63%, and 69%, respectively) and less frequently was surgery (30%, 25%, 13%, and 9%, respectively). Multivariate models revealed little variation in the probability of aggressive treatment by comorbidity status within age subgroups despite substantial differences in mortality. CONCLUSIONS: Men aged <80 years at diagnosis who have life expectancies <10 years often receive aggressive treatment for low‐risk and intermediate‐risk prostate cancer, mostly with radiation therapy. Cancer 2014;120:3642–3650. © 2014 American Cancer Society . Abstract : This retrospective study characterizes treatment patterns for early stage prostate cancer according to life expectancy in a population‐based cohort of US men. Men aged <80 years at diagnosis who have a life expectancy less than 10 years often receive aggressive treatment (mostly radiation therapy) for low‐risk and intermediate‐risk prostate cancer.